EFFECTIVE PUBLIC SPEAKING - Umar - Farouk (Politeknik Negeri Semarang, 2015)
Experts of Communication state thatcommunication is the backbone ofmanagement. This indicates the strategic rolesof communication. Management which is notsupported by effective communication willfail to achieve its goals or targets. Effectivecommunication and effective managment islike the two sides of a coin.They cannot beseperated. Effective public speaking as a partof effective communication give itssignificant contributions to effectivecommunication process in a businessorganizations. This article discusses severaltips of effective public speaking to developcommunication skills which are exremelyneeded to develop business organizations.